Electronic correlations in epitaxial CrN thin film - Shailesh Kalal; Sanjay Nayak; Sophia Sahoo; Rajeev Joshi; Ram Janay Choudhary; Rajeev Rawat; Mukul Gupta (Scientific Reports, 2023)
Abstract Chromium nitride (CrN) spurred enormous interest due to its coupled magnetostructural and unique metal-insulator transition. The underneath electronic structure of CrN remains elusive. Herein, the electronic structure of epitaxial CrN thin film has been explored by employing resonant photoemission spectroscopy (RPES) and X-ray absorption near edge spectroscopy study in combination with the first-principles calculations. The RPES study indicates the presence of a charge-transfer screened 3 $$d ^n{\underline{L}}$$ d n L ̲ ( $$L$$ L : hole in the N-2 $$p$$ p ) and 3 $$d ^{n-1}$$ d n - 1 final-states in the valence band regime. The combined experimental electronic structure along with the orbital resolved electronic density of states from the first-principles calculations reveals the presence of Cr(3 $$d$$ d )-N(2 $$p$$ p ) hybridized (3 $$d ^n{\underline{L}}$$ d n L ̲ ) states between lower Hubbard (3 $$d ^{n-1}$$ d n - 1 ) and upper Hubbard (3 $$d ^{n+1}$$ d n + 1 ) bands with onsite Coulomb repulsion energy (U) and charge-transfer energy ( $$Δ$$ Δ ) estimated as $$≈$$ ≈ 4.5 and 3.6 eV, respectively. It verifies the participation of ligand (N-2 $$p$$ p ) states in low energy charge fluctuations and provides concrete evidence for the charge-transfer ( $$Δ<$$ Δ < U) insulating nature of CrN thin film.